The Role of European Integration in Ensuring Economic Security - A. Stavytskyy (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper considers the issue of ensuring the level of economic security in Europe. Based on the panel gravity model, a regression was estimated for 49 European countries for 1991–2017. The investigation tested six different hypothesis about the channels of dissimilation of economic security level in Europe. The results provided an opportunity to determine the factors affecting the spread of a high level of economic security to neighbouring countries. It was stated that some factors play an important role in the process of exchanging best practices, technologies, human capital, etc. In particular, such factors can be mentioned: the economic security index of the neighbouring country, the difference in the indices of economic security between countries, the distance between countries, the existence of common borders, the country's participation in the European Union, the introduction of the euro in the country. It was shown that European countries have not yet exhausted the potential of developing their own economic security. For example, the expansion of the European Union, of course, subject to the principles of its functioning, can increase the general security level by about 1,5 %. Also, it was stated that distances cease to play a decisive role for the spreading the technologies, goods, services. This means that taking into account the development of Europe's transport infrastructure, it is possible to quickly disseminate the latest trends in economic security among countries. Economic growth and equalization in economic conditions offset the differences between countries. The growth of the economic security index in neighbouring countries is sufficiently significant. Thus, it is beneficial for all countries to have prosperous neighbours around them. At the same time, an increase in the economic security index is possible only with a significant increase in competition.